Menulis Cerita Pendek dengan Model Pembelajaran “CANTIK” Bagi Siswa SMA Negeri 1 Tawangsari Tahun Pelajaran 2019/2020 - Yuni Setyaningsih (JURNAL PENDIDIKAN, 2021)
This study aims to 1) find out the technique of writing short stories with the "CANTIK" learning model, 2) improve students' skills in writing short stories. In this study, the subjects were teachers and students of class XI MIPA1 SMA N 1 Tawangsari in the even semester of the 2019/2020 school year. The object of research in general is the implementation of learning to write short stories. The data obtained by the technique of giving short story writing assignments, observation and documentation. The data were analyzed using a qualitative description method, namely data presentation and conclusion drawing/verification. The results showed that learning to write short stories in class XI MIPA1 SMA N 1 Tawangsari in the even semester of the 2019/2020 school year was carried out based on the 2013 Curriculum, the Indonesian language learning syllabus for class XI, and was carried out according to the Indonesian RPP for short story text teaching materials. The obstacles faced in learning to write short stories are 1) the implementation of the right learning model in learning to write short stories, 2) the low motivation of students in participating in short story writing lessons, 3) decreased concentration of students when learning Indonesian is scheduled in the final hours. learning. The ways to overcome these obstacles are 1) the application of learning methods to write short stories that are appropriate and interesting for students, 2) provide motivation and enlightenment to students about the benefits of having the ability to write short stories in everyday life. 4) variations in the allocation of learning schedules for writing short stories.